PENGARUH BRAND IMAGE, DISTRIBUSI, DAN PROMOSI TERHADAP KEPUTUSAN KONSUMEN MENGGUNAKAN JASA PENGIRIMAN J&T EXPRESS DI DROP POINT KRAKATAU MEDAN - Darwin; Yayuk Yuliana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2022)
This study aims to examine the effect of brand image (X1), distribution (X2), and promotion (X3) on consumer decisions (Y) to use J&T Express delivery services at Drop Point Krakatau Medan. The data used is data using probability sampling method, with a total sample of 98 respondents. The analysis method of this research uses multiple linear regression. The classical assumption test used has met the specified criteria, the t-test (partial test) shows that the brand image, distribution and promotion variables have a positive and significant effect on consumer decisions because the tcount > ttable brand image is 10.727 > 1.664, the tcount > ttable distribution of 2.698 > 1.664 and the value of tcount > ttable promotion of 11.872 > 1.664. From the results of the f test (simultaneous test) the value of fcount > ftable is 61,691 > 3.09, then this shows that brand image, distribution and promotion together have a significant effect on consumer decisions to use J&T Express delivery services at Drop Point Krakatau Medan.